Transcendence How Humans Evolved through Fire, Language, Beauty, and Time - Gaia Vince (United Kingdom Penguin, 2020)
Humans are a planet-altering force. Gaia Vince argues that our unique ability - compared with other species - to determine the course of our own destiny rests on a special relationship between our genes, environment and culture going back into deep time. It is our collective culture, rather than our individual intelligence, that makes humans unique. Vince shows how four evolutionary drivers - Fire, Language, Beauty and Time - are further transforming our species into a transcendent superorganism: a hyper-cooperative mass of humanity that she calls Homo omnis. Drawing on leading-edge advances in population genetics, archaeology, palaeontology and neuroscience, Transcendence compels us to reimagine ourselves, showing us to be on the brink of something grander - and potentially more destructive.
Includes Index
Keywords: Social history; Evolutionary psychology; Human evolution